Soil moisture sensors for sustainable water management in field crop production: A review of advances and application challenges - Kuunya, Ronald; Osman, Magdoline Mustafa Ahmed; Ssemugenze, Brian; Gumisiriya, Costa; Ragán, Péter (Acta Agraria Debreceniensis, 2025)
Efficient water management is essential for sustainable production of field crops amid climate change, population growth, and water scarcity. Traditional irrigation practices often lead to water use inefficiency, which harms soil health and reduces yields. To address this, reviewing previous studies on soil moisture sensors provides important context and guidance. Literature from Scopus, Google Scholar, and WoS (2019–2025) on soil moisture sensors for sustainable water management in field crops was screened. Out of 244 retrieved publications, 79 met the inclusion criteria with a focus on sensor technologies, applications, advances, and challenges, analysed thematically for research gaps and insights. Based on the findings, soil moisture sensors boost water management, improve yields of field crops, and support sustainable agriculture. However, hindrances related to high costs, lack of awareness, technical complexity, calibration needs, energy challenges, data interpretation difficulties, and compatibility problems hinder effective soil moisture sensor results. Integrating soil moisture sensors with decision-support tools optimises water use and protects soil health to promote long-term productivity under climate variability. Future research should strategise on the development of low-cost, reliable soil moisture sensors with technology subsidies, training, policy support, durability, integration, and simple data to empower farmers to adopt precision water management.